2012
DOI: 10.1039/c2cp23492k
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-optical properties of Cd1−xMnxS nanoparticles: influences of magnetic doping, Mn2+ ions localization, and quantum confinement

Abstract: Cd(1-x)Mn(x)S nanoparticles (NPs) were successfully grown in a glass matrix and investigated by optical absorption (OA), magnetic circularly polarized photoluminescence (MCPL) measurements, and magnetic force microscopy (MFM). The room temperature OA spectra have revealed the formation of two groups of Cd(1-x)Mn(x)S NPs with different sizes: bulk-like nanocrystals (NCs) and quantum dots (QDs). The MCPL spectra were recorded at 2.0 K with several magnetic fields up to 15 T, allowing a detailed comparison betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…It was recently demonstrated that the magnetization of Cd 1−x Mn x S QDs cannot be probed by MFM measurements when the magnetic ions (Mn 2+ ) are located near to the dot surface . Therefore, it is concluded that the sp‐d exchange interaction is larger for Cd 1−x Co x S QDs than for Cd 1−x Mn x S QDs, in agreement with the behavior of the corresponding bulk materials .…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…It was recently demonstrated that the magnetization of Cd 1−x Mn x S QDs cannot be probed by MFM measurements when the magnetic ions (Mn 2+ ) are located near to the dot surface . Therefore, it is concluded that the sp‐d exchange interaction is larger for Cd 1−x Co x S QDs than for Cd 1−x Mn x S QDs, in agreement with the behavior of the corresponding bulk materials .…”
Section: Resultsmentioning
confidence: 69%
“…Therefore, it is concluded that the sp‐d exchange interaction is larger for Cd 1−x Co x S QDs than for Cd 1−x Mn x S QDs, in agreement with the behavior of the corresponding bulk materials . This accumulation of Co 2+ ions at sites near the Cd 1−x Co x S QD surface can be understood as a direct result of the self‐purification effect, which is the dominant mechanism controlling the doping in semiconductor QDs grown by the melting‐nucleation synthesis route because of the relatively high temperature used while thermally annealing the samples …”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…This SNAB glass matrix, developed by NO Dantas, proved to be an excellent host for the growth of various types of quantum dots synthesized in the group, which presents glass transition temperature around at 798.15 K. 24 The optical properties of the quantum dots are modified with the incorporation of magnetic ions due to the sp-d hybridization that occur between the electronic subsystems. [25][26][27] This exchange interaction causes a blueshift in the peak energy with increasing x of Cd 1Àx Mn x Te compared to CdTe QDs. 28 QDs.…”
mentioning
confidence: 99%